Effect of Processing Parameters on the Morphology and Mechanical Properties of PMMA Electrospun Fibre - Sulong, AB; Akhtar, MN; Ab Karim, S; Azhari, CH (PENERBIT UNIV KEBANGSAAN MALAYSIA, 2024)
Indexed by WOS